Possibility of filter materials for phosphorus removal from domestic wastewater - Adnan, Suraya Hani; Abd Roni, Norwardatun; Hamidon, Nuramidah (Penerbit UTHM, 2020)
Phosphorus is the form of phosphate is a normal part of the environment. It occurs in the form of phosphate containing rocks and as the excretory and decay products of plants and animals. Controlling phosphorus discharged from municipal and industrial wastewater treatment plants is a key factor in preventing eutrophication of surface waters. Phosphorous is one of the major nutrients contributing in the increased eutrophication of lakes and natural waters. One of the major sources of phosphorus development is from wastewater discharge. Its presence causes many water quality problems including increased purification costs, decreased recreational and loss of livestock. A research has been conducted on the production of phosphorus. The research show that the basic cause of water eutrophication is more connected to an imbalance in the load of nitrogen and phosphorus with respect to silica [1].